The impact of competition effort on the vital capacity of football players according to the playing positions. - فراس عبدالحميد خالد (الرياضة المعاصرة)
The study focused on identifying the effect of competition effort on the level of vital capacity of young football players according to their playing centers. The researchers selected their sample from the (82) Fallujah clubs, the Golan club and the youth football stamina club, which numbered (82). The research problem focused on the lack of clarity of vision in identifying  The level of respiratory competence represented by the vital capacity of young football players according to their playing centers. The study aimed to know the immediate effect of competition effort on the level of vital capacity of young football players and to identify the level of that variable according to the centers of playing football.  For young football players and the existence of differences in the results of the post-test in the level of vital capacity of young players according to the centers of playing football. The researchers used the descriptive approach (case study) and conducted their pre and post tests according to the scientific foundations. The researchers concluded that the match effort has an effect on the level of vital capacity for all  Players are in different playing lines and that effect on the level of vital capacity was varied according to  The lines of play and the lines most affected was the midfield, followed by the defense line, then the offensive line and finally the goalkeepers. The researchers recommended that additional studies be conducted to know the effect of the match effort on other variables of the respiratory system and other functional devices and to conduct other studies to find out the effect of competition effort on other groups such as juniors and   advanced.